2009
DOI: 10.1016/j.jtcvs.2009.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Two-year neurodevelopmental outcomes of infants undergoing neonatal cardiac surgery for interrupted aortic arch: A descriptive analysis

Abstract: The neurodevelopmental indices of children who have undergone neonatal cardiac surgery for interrupted aortic arch are below normative values; those of children with chromosomal abnormalities are even lower. For children without a chromosomal abnormality, longer deep hypothermic circulatory arrest times and low Apgar scores predict lower mental developmental indices at 18 to 24 months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…As an unexpected finding, we found that aboriginal children were markedly over represented in this group compared with the rest of our population. We have also published on the outcomes of children with interrupted aortic arch without chromosomal anomalies [66] and children with complex cardiac surgery in the neonatal period who have deletion 22q11.2 [7]. The latter are at a high risk for adverse neurodevelopmental outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…As an unexpected finding, we found that aboriginal children were markedly over represented in this group compared with the rest of our population. We have also published on the outcomes of children with interrupted aortic arch without chromosomal anomalies [66] and children with complex cardiac surgery in the neonatal period who have deletion 22q11.2 [7]. The latter are at a high risk for adverse neurodevelopmental outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Serious CHDs were studied collectively, with the exception of IAA-B, due to a previously reported association of ID with 22q11.2DS in IAA. 11 We also studied neonatal cyanosis unexplained by either neonatal hypocalcemia or serious CHD. We recorded family history of ID (n = 4) and epilepsy (n = 2) in first-degree relatives of subjects, excluding relatives with proven or probable 22q11.2DS.…”
Section: Evaluationsmentioning
confidence: 99%
“…Previous research on IAA focused on early mortality and re-intervention rate, demonstrating variable perioperative mortality[2, 4-6], with most recent reporting mortality of 3.6% at 2 years[7] and 39% at 21 years[6]. We report data on survivors and cannot comment on how mortality in our cohort compares with previous studies.…”
Section: Discussionmentioning
confidence: 72%
“…For both strategies, risks of mortality and re-intervention have been described[2-6]. To date, other aspects of the clinical status of subjects who survive surgery have received less attention, other than a single study that demonstrated worse neurodevelopmental outcomes in IAA patients at 2 years of age[7]. In this study, we sought to provide a cross-sectional multi-dimensional characterization of clinical status in this population in school-age and adolescent survivors after operative correction as well as retrospective data regarding their rates of re-intervention and utilization of health care resources.…”
Section: Introductionmentioning
confidence: 99%